Inhibitory effect of unicellular green algae (Chlorella vulgaris) water extract on allergic immune response. (5th April 2013) - Bae, Min‐Jung; Shin, Hee Soon; Chai, Ok Hee; Han, Jae‐Gab; Shon, Dong‐Hwa
Abstract Background Chlorella is used as a functional food in East Asia and has been shown to enhance immune system function. However, there has been no direct evidence of the suppressive effect of a hot water extract of Chlorella vulgaris (CVE) on histamine‐mediated allergic responses. Results The antihistamine activity of CVE was analysed using rat peritoneal mast cells (RPMCs) stimulated by compound 48/80. For in vivo verification, ovalbumin (OVA)‐immunised BALB/c mice were treated with CVE orally. Serum immunoglobulin E (IgE) levels and splenocyte cytokine levels were determined by enzyme‐linked immunosorbent assay (ELISA). CVE prevented histamine release through degranulation of mast cells by blocking the uptake of extracellular Ca2+ into RPMCs. Moreover, CVE administration inhibited serum IgE overproduction by OVA via induction of T helper 1 (Th1) skewing that was dependent on interferon‐γ (IFN‐γ) and interleukin 12 (IL‐12) secretion. Conclusion The results of this study clearly demonstrate that CVE acts as an antiallergic dietary agent by suppressing histamine release via its enhancive effect on Th1‐related responses. © 2013 Society of Chemical Industry